218k views
4 votes
T=√k(k-b)(k-m).... make b the subject of the formula​

User Ashar
by
6.0k points

1 Answer

7 votes

Answer:

b = -T²/k(k-m) + k

Explanation:

Given the equation T =√k(k-b)(k-m), we are to make b the subject of the formula​

Square both sides

T² = (√k(k-b)(k-m))²

T² = k(k-b)(k-m)

T²/k(k-m) = k-b

Rearrange

k - b = T²/k(k-m)

b - k = - T²/k(k-m)

Add j=k to both sides

b - k + k = - T²/k(k-m) + k

b = -T²/k(k-m) + k

This gives the required expression

User Gergo Erdosi
by
6.9k points